Factors Associated with Amoebic Dysentery in Captive Non-Human Primates of The Mefou Primate Sanctuary - Gery Wamba; Clarisse Njua-Yafi; Jeannette Tombi (The International Journal of Tropical Veterinary and Biomedical Research, 2022)
Primates are known to harbour different gastrointestinal parasite species that affect their survival and reproductive activity. Entamoeba histolytica infects humans predominantly as well as non-human (NH) primates causing amoebiasis. Amoebic dysentery is common amongst non-human primates in captive sites. The purpose of the study was to evaluate the risk factors associated with the prevalence of amoebic dysentery in captive NH primates of the Mefou Primate Sanctuary (MPS) in Cameroon. The faecal samples of 277 NH primates were analysed by qualitative (direct smear and evergreen kit sedimentation technique) coprology from January to July 2019. Factors such as habitat type, keeper’s age and level of education were assessed to evaluate their effect on the prevalence of amoebic dysentery. The prevalence of Entamoeba histolytica was 46.2% (P=0,079 and χ2=18.13). E histolytica was the most predominant parasite species detected and it was present in all instances of mixed parasite infections. Amongst the NH primates positive for E. histolytica, 28 suffered from amoebic dysentery giving a prevalence of 21.9% and one of the infected primates (Cercopithecus pogonias) actually died from amoebic dysentery. The prevalence of mixed infections was significantly lower amongst NH primates living in outdoor enclosures compared to those living in other habitat types (P=0.015, χ2=10.46). The rate of re-infection was significantly higher amongst NH primates under the care of keepers with the lowest (primary school) level of education (P=0.001, χ2=13.09) on one hand and of older keepers (≥50s) (P = 0.008, χ2=13.708) on the other hand. This study shows that amoebic dysentery is a cause for a major concern in the MPS. The housing conditions of the NH primates at the sanctuary, the keeper’s age and level of education were important factors that influenced the prevalence of amoebic dysentery. Adequate measures should be put in place to address the situation.